2003
DOI: 10.1016/s0195-668x(02)00826-6
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of extensive coronary calcium quantities in symptomatic males?a 5-year follow-up study

Abstract: Symptomatic males with extensive CSs carry an even higher risk for future events than other symptomatic males with advanced CAD. In these patients, EBT-based calcified plaque burden and angiographic indices of disease severity may have a complementary role in predicting future cardiovascular events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 26 publications
0
18
0
3
Order By: Relevance
“…Slight difference in results may be due to difference in size of study population. Arad Y et al (2005) [7] and Mohlenkamp et al [8] in their studies observed that coronary calcification was a strong and independent predictor of CAD in all age groups and the risk of CAD increased with the increasing calcium score. It was also found to predict the risk of CAD events independenly of standard risk factors.…”
Section: Discussionmentioning
confidence: 96%
“…Slight difference in results may be due to difference in size of study population. Arad Y et al (2005) [7] and Mohlenkamp et al [8] in their studies observed that coronary calcification was a strong and independent predictor of CAD in all age groups and the risk of CAD increased with the increasing calcium score. It was also found to predict the risk of CAD events independenly of standard risk factors.…”
Section: Discussionmentioning
confidence: 96%
“…The difference log(DSCT+1)-log(EBCT+1) was significantly negative by paired t-test for each replicate (1,2), and for the mean of replicates (3) We additionally performed ordinary linear regression (OLR) of log(DSCT+1) on log(EBCT+1) for each reader and the pooled data (1, 2, 3). While the intercept was always compatible with zero, the slope was 0.938 (0.…”
Section: Methods Comparison Electron-beam Ct Vs Dualsource Ctmentioning
confidence: 99%
“…On the Agatston score scale, a correction factor from DSCT to EBCT based on the mean of replicates (3) from PBR would read: log(DSCT+1)5log(EBCT+1)60.975: EBCT5(DSCT+1) 1.026 -1. Consecutively, we applied the correction factor to the DSCT scores.…”
Section: Correction Factor For Dual-source Ctmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a linear relationship between the amount of coronary calcium and coronary atherosclerosis, that is, the more coronary calcium the higher the likelihood of coronary stenosis (Rumberger et al 1995), and proportionally prognostic -the higher the calcium score the greater the likelihood of coronary events (O'Rourke et al 2000). Moehlenkamp and colleagues recently demonstrated that coronary calcium scoring not only adds prognostic value to the Framingham risk model, but also that it's value is greater than hsCRP (Mohlenkamp et al 2003). Also the recent randomized Eisner Trial demonstrated that coronary calcium testing leads to better downstream control of coronary risk factors (Rozanski et al 2011).…”
Section: Application Of Coronary Calcium Scoringmentioning
confidence: 99%